Wittgenstein y Chomsky en contrapunto: notas epistemológicas y metodológicas en torno al lenguaje, conocimiento y comunicación. - Rivano Fischer, Emilio (2012)
In this essay, Wittgensteinian and Chomskyan doctrines and arguments, particularly methodological and epistemological ones, combine to introduce current perspectives on human language and human cognition.